The storm [large type] - Cussler, Clive (Cussler, Clive. NUMA files., 2012)
Kurt Austin and Joe Zavala investigate the smoldering hulk of a NUMA research vessel in the Indian Ocean and soon uncover an audacious scheme to permanently alter the weather on a global scale, killing millions.